2020
DOI: 10.1021/acs.energyfuels.0c03301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Asphaltene Stability of a Wide Range of Mexican Crude Oils

Abstract: Appropriate prediction of asphaltene stability can anticipate operational problems such as plugging of lines and process equipment (pumps, heat exchangers, separation tanks, among others), thus assuring the production, processing, transportation, and storage of petroleum. In the present study, the physical and chemical properties of a series of Mexican crude oils with American Petroleum Institute (API) gravity ranging from 10 to 52 were determined. Based on saturate, aromatic, resin and asphaltene (SARA) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Both Comparisons reveal that CII is better suited for indicating crude oil incompatibility. Also a Mexican region crude comparison revealed that CII and CSI, has much better accuracy of prediction . The methods based on the comparison of several parameters, such as QAA and SCP, show the greatest number of correct predictions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Both Comparisons reveal that CII is better suited for indicating crude oil incompatibility. Also a Mexican region crude comparison revealed that CII and CSI, has much better accuracy of prediction . The methods based on the comparison of several parameters, such as QAA and SCP, show the greatest number of correct predictions.…”
Section: Discussionmentioning
confidence: 97%
“…Also a Mexican region crude comparison revealed that CII and CSI, has much better accuracy of prediction. 70 The methods based on the comparison of several parameters, such as QAA and SCP, show the greatest number of correct predictions. Predictive methods based on the SARA analysis are characterized by simplicity, but as experience shows, each of them individually does not guarantee satisfactory results of compatibility prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that resins have the greatest impact on the stability of asphaltene molecules in crude oil as they contribute to smaller aggregate formation and thereby prevent separation of the asphaltene molecules. ,, Resins are also polar components of crude oil and are soluble in pentane and heptane but insoluble in propane. Structurally, resins are akin to asphaltenes, but they have a higher H/C ratio (1.2–1.7), lower aromaticity, and lower molecular weight compared to asphaltenes. ,, Relatively longer aliphatic side chains and smaller chromophores contribute to higher solubility of resins in aliphatic solvents .…”
Section: Asphaltene Structurementioning
confidence: 99%
“…Resins are also another type of polar crude oil component having a profound influence on the stability behavior of asphaltenes in crude oils as they can prevent the separation of the asphaltene molecules. In terms of structure, resins are very similar to asphaltenes; however, they have a lower molecular weight (MW) (<1000 g/mol) and higher hydrogen/carbon (H/C) ratio (1.2–1.7). , Moreover, as compared to asphaltenes, resins have smaller chromophores and relatively longer aliphatic side chains, which increase their solubility in aliphatic solvents . The molecular interaction between asphaltenes and resins and their ratio with respect to other components in crude oils are vital for the stabilization of crude oil emulsions.…”
Section: Introductionmentioning
confidence: 99%